Determination of putative virulence factors among clinical isolates of enterococci isolated from a military hospital in the eastern province of Saudi Arabia - George, Siju Kankalil; Suseela, M. R.; El Safi, Saleh; El Nagi, El Moiez Ali; Adam, Ahmed Adlan Mohammed; Jacob, Ashly Mary; Al-Maqati, Thekra; Al Shehri, Abdullah; K. S., Harish Kumar (International Journal of Research in Medical Sciences, 2020)
Background: The pathogenic potential of enterococci to produce life-threatening infections is well-documented. The scientific community has, of late, evinced a renewed interest in the putative virulence factors of enterococci. Objective of the study was to determine the putative virulence factors of clinically isolated Enterococcus species from a military hospital and to describe the association between virulence factors and vancomycin susceptibility. Methods: A total of 245 enterococci were isolated from clinical samples collected from KFMMC, a leading military hospital in the eastern province of Saudi Arabia. Following species identification and antimicrobial susceptibility testing using the Vitek 2 system; the isolates were tested for the production of caseinase, gelatinase, biofilm, and presence of haemolysin. Results: Among the enterococcal isolates, 36.7% produced caseinase, 38% produced gelatinase, 24.1% exhibited biofilm formation, and 30.6% were positive for haemolytic activity. A significant association between vancomycin susceptibility patterns and the virulence factors, gelatinase and haemolytic activity, were noted. No significant associations were observed between vancomycin susceptibility patterns and the presence of caseinase or the formation of biofilms. Conclusions: Virulence factors are invariably produced by several clinical isolates of enterococci in our hospital, and some virulence factors are associated with vancomycin susceptibility.